Network Security: Attacks, Tools and Techniques (International Journal of Scientific Research and Management (IJSRM), 2015)
Network security is main issue of this generation of computing because many types of attacks are increasing day by day. Establishing a network is not a big issue for network administrators but protecting the entire network is a big issue. There are various methods and tools are available today for destroying the existing network. In this paper we mainly emphasize on the network security also we present some major issues that can affect our network.